BRAND TRUST MEMEDIASI PENGARUH SOCIAL MEDIA MARKETING DAN CELEBRITY ENDORSER TERHADAP PURCHASE DECISION - Ritanti Aulia Muswara; Hasnah Rimiyati (Yayasan Insani Mandiri Santani, 2026)
This study aims to analyze the influence of social media marketing and celebrity endorsers on purchase decisions through band trust in Glad2Glow skincare consumers in the Shopee marketplace in the Special Region of Yogyakarta. The subjects in this study were consumers who had purchased Glad2Glow. The sample consisted of 160 respondents selected using a purposive sampling method with the criteria of being at least 17 years old, having purchased and used Glad2Glow skincare in the last 6 months through the Shopee marketplace, consumers domiciled in the Special Region of Yogyakarta, having seen Syifa Hadju promote Glad2Glow skincare on Instagram. The analysis method used Structural Equation Modeling Partial Least Squares (SEM PLS) with Smart PLS software. Based on the data analysis that has been done, the results show that social media marketing has a positive and significant effect on band trust. Celebrity endorsers have a positive and significant effect on band trust. Brand trust has a positive and significant effect on purchase decisions. Social media marketing has a positive and significant effect on purchase decisions. Celebrity endorsers have a direct positive and significant effect on purchase decisions. Brands continue to mediate social media marketing on purchase decisions. Brand trust mediates celebrity endorsers towards purchase decisions. Keywords: purchase decision; brand trust; celebrity endorser; social media marketing.